Model Kepemimpinan Demokratis dan Kharismatik: Studi Kasus di MAN dan MA Qosim Al Hadi Semarang - Zainudin Zainudin; Samidi Samidi (Balai Penelitian dan Pengembangan Agama Semarang, 2022)
The principal at madrasah in the education system has a very important role as a determinant of whether a school is progressing or not. This study specifically aims to determine the madrasa school leadership model at MAN and MA Qasim Al Hadi in Semarang. The research on the two madrasah model includes qualitative research, which takes the research locus of public and private Madrasah Aliyah. The results showed that the MAN Semarang in leadership adheres to a bureaucratic democratic system of democracy. This means that everything is done in accordance with standard operating procedures with modern management. While the leadership model at MA Qasim Al Hadi, the education system is strongly influenced by the central figure who has been appointed by the foundation as the head of the school (kiai). It is the figure of the kiai who spurs all movements in the educational process. Implementatively, the leadership model of the Head of MA Qosim Al Hadi can be seen from his personality and democratic character. Apart from being based on personality type, it also depends on the status of the madrasa (private). Thus the leadership model of MA Qosim Al Hadi can be said to be a charismatic leadership pattern.